MENUMBUHKEMBANGKAN SIKAP PEDULI LINGKUNGAN PADA SISWA SMPN 1 SUMBANG MELALUI BUDIDAYA AQUAPONIK - Rahayu, Diana Retna (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2021)
Environmental education can be applied to attitudes and behavior from an early age. This service activity is carried out to increase the understanding and awareness of SMPN 1 Sumbang students about the environment through productive aquaponic cultivation. Besides that, it also develops student character, so that they are active in protecting the surrounding environment through positive activities during the Covid 19 pandemic. Student responses were carried out by pre and post test with six questions. The results of the activity showed a change in behavior and an understanding level of 60%, this shows that the introduction of aquaponic cultivation can help students better understand the importance of protecting the environment both at school and at home.